Post-traumatic stress, awareness, and preparedness among Thai dental students after a century-scale regional earthquake - Tanit Arunratanothai; Thanaphum Osathanon; Nareudee Limpuangthip (PLoS ONE, 2026)
Objectives To assess responses, post-traumatic stress level, and awareness and preparedness among Thai dental students following the Sagaing earthquake, and to identify the factors associated with their traumatic stress level. Methods A questionnaire survey was distributed via Google Form in April 2025 to dental students enrolled at the dental school. The questionnaire consisted of four sections: (1) demographic information; (2) experiences and responses during the earthquake; (3) post-traumatic stress, assessed using the post-earthquake trauma level determination scale; and (4) earthquake awareness and preparedness, assessed using the sustainable scale of earthquake awareness, both using five-point Likert scales. Associations between trauma scores and related variables were analysed using the Wilcoxon Rank Sum or the Kruskal–Wallis test, and multivariable negative binomial regression. Results Of 921 students, 287 completed the questionnaire. Initial perceptions during the earthquake were mainly dizziness and fatigue. Immediate responses included drop–cover–hold and stairway evacuation, with most students first grabbing mobile phones, followed by bags and laptops/tablets. Reported reactions focused on concern for loved ones, anxiety about future quakes, and greater appreciation of life and relationships. Multivariable analysis showed that living on the 8th floor or higher was significantly associated with higher post-traumatic stress scores compared to living in houses or lower floors. Conclusion The earthquake caused low post-traumatic stress among Thai dental students, though stress was higher in high-rise residents. It increased appreciation of life and relationships. While the faculty response was effective, stronger city- and national-level disaster management is needed for future safety.